Hemoglobin levels and coronary heart disease risk by age, race, and sex in the reasons for geographic and racial differences in stroke study (REGARDS). Issue 3 (22nd December 2019) - Houghton, Damon E.; Koh, Insu; Ellis, Alicia; Key, Nigel S.; Douce, Daniel R.; Howard, George; Cushman, Mary; Safford, Monika; Zakai, Neil A.
Abstract: Higher and lower hemoglobin concentrations are associated with coronary heart disease (CHD), but whether this risk is consistent across age, sex, and race is unclear. The Reasons for Geographic And Racial Differences in Stroke (REGARDS) study is an observational cohort study of 30 239 black, and white, adults aged 45 and older recruited 2003‐7. Participants were included if they had hemoglobin measures, were CHD‐free at baseline, and had all baseline variables. The primary outcome was incident CHD. Multivariable Cox proportional hazards models were used to estimate the hazard ratios (HR) and 95% confidence intervals (CI) for incident CHD by hemoglobin concentration. This was expressed as a continuous variable and divided into age‐, sex‐, and race‐specific quintiles. The 16 332 participants were included, contributing 114 362 person‐years of follow‐up and 915 incident CHD events. The mean age was 63 years, 35% were male, 41% were black, and the mean baseline hemoglobin was 13.6 g/dL (SD 1.4). A significant non‐linear association between hemoglobin and CHD was identified ( P < .001). This association differed significantly by race ( P = .025) but not by sex or age. In whites, the risk for incident CHD was higher in the lowest (HR 2.28, 95% CI 1.61, 3.33) and highest (HR 1.94, 95% CI 1.35, 2.79) hemoglobin quintiles relative to the third quintile. For blacks, only those in the lowest hemoglobin quintile had an increased risk for incident CHD events (HR 1.70, 95% CI 1.20, 2.41). Hemoglobin is an independent risk factor for CHD in whites and blacks but with different hemoglobin concentrations conferring different risks.